Investigation of Effect of Dual Fuel Injection Stages on Combustion Parameters in a Diesel Engine Using Ethanol-Butan-2-ol-Fossil Diesel Blends - VARGÜN, MUSTAFA (My University, 2022)
The present study aims to evaluate on the effect of different injection strategies on the combustion and emission characteristics in a diesel engine with fueled ethanol-butan-2-ol-diesel fuel blends. The most critical problem in the use of fossil-based diesel fuel (FBDF) and ethanol mixtures as an alternative fuel is the phase separation that occurs in a very short time. Therefore, there is a need to use a stabilizer to maintain the homogeneity of the mixture for long-term test conditions. In this study, butan-2-ol (2-butanol) was added to the fuel mixtures as a co-solvent to prevent the phase separation in ethanol-FBDF mixtures. It was observed that the homogeneity of the ethanol and FBDF mixtures was ensured for a long time by adding butan-2-ol up to 20% of the ethanol in the mixture. In the experiments, three different states (main, 5% pilot and 10% pilot) were developed by changing the fuel injection rate shapes. Engine tests have been performed by spraying a total of 45 mg fuel for each fuel per cycle and by charging fresh air into the cylinder at constant temperature and pressure conditions. As the results of this study, the highest maximum cylinder gas pressure with FBDF was observed in a 10% pilot injection application. With the use of ethanol-butan-2-ol-FBDF blends, a decrease in CO, CO2 and NH3 emissions were detected, while NOx emission increased. The lowest combustion noise was seen with 15% ethanol + 3% butan-2-ol + 82% FBDF (E15B3) and 20% ethanol + 4% butan-2-ol + 76% FBDF (E20B4) fuels as 84 dB. A sharp increase in heat release rate was observed using E15B3 in 5% pilot injection compared to FBDF.
Keywords: Temel Bilimler; Natural Sciences; ÇOK DİSİPLİNLİ BİLİMLER; Doğa Bilimleri Genel; Temel Bilimler (SCI); MULTIDISCIPLINARY SCIENCES; NATURAL SCIENCES, GENERAL; Natural Sciences (SCI); Multidisipliner; Multidisciplinary; Ethanol; 2-butanol; Diesel engine; Dual injection; Combustion noise; Emission; EMISSION CHARACTERISTICS; BUTANOL-ETHANOL; PERFORMANCE; NUMBER; NOISE